Diptera, Psychodidae, Phlebotominae Rondani, 1840: Range extension and new records from lowland Bolivia. - Brazil, R. P.; Passos, W. L.; Brazil, B. G.; Temeljkovitch, M.; Andrade-Filho, J. D. (Check List, 2010)
During a field trip to the town of El Carmen in de Department of Santa Cruz we captured 108 specimens ofPhlebotominae (Diptera: Psychodidae). Among the specimens examined, we found five species of sand fly comprising fourgenera. Four species (Lutzomyia cruzi, Lutzomyia forattinii, Evandromyia corumbaensis, Expapillata cerradincola) are newrecords which increased the number of species known to occur in Bolivia from 117 to 121.